1983
DOI: 10.1111/j.1751-0813.1983.tb05971.x
|View full text |Cite
|
Sign up to set email alerts
|

Inherited copper toxicosis in Bedlington terriers

Abstract: Chronic hepatitis and increased hepatic copper concentrations, from 1,600 to 6,361 micrograms/g dry tissue were found in 4 related, Australian-bred Bedlington terriers. Two dogs were asymptomatic and 2 were clinically ill with signs referable to liver dysfunction. Two dogs were treated with d-penicillamine. After one year there was no improvement in the histopathological liver changes in either dog or significant lowering of hepatic copper level in one dog.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…Affected dogs may exhibit various clinical signs associated with liver disease, and, in addition, a few have intravascular haemolysis (Hardy and Stevens 1977;Twedt et a1 1979). Robertson et a/ (1983) have recently described copper storage disease in 4 Bedlington terriers in Australia and we report here an additional case in which the presenting complaint was intravascular haemolysis.…”
Section: Introductionmentioning
confidence: 73%
“…Affected dogs may exhibit various clinical signs associated with liver disease, and, in addition, a few have intravascular haemolysis (Hardy and Stevens 1977;Twedt et a1 1979). Robertson et a/ (1983) have recently described copper storage disease in 4 Bedlington terriers in Australia and we report here an additional case in which the presenting complaint was intravascular haemolysis.…”
Section: Introductionmentioning
confidence: 73%
“…The most common toxic injury causing CH in dogs is a consequence of hepatic copper (Cu) excess . Copper‐associated CH (CuCH) may develop in any breed, including mixed breeds, but the Bedlington Terrier (BT), Dalmatian, Labrador Retriever (LR), Doberman Pinscher, and West Highland White Terrier are predisposed.…”
Section: Etiologymentioning
confidence: 99%
“…Inherited copper toxicosis was first identified in Bedlington terrier in USA, in 1975(Hardy et al 1975 and has since been reported in other countries including Australia (Eriksson 1983;Robertson et al 1983;Kelly et al 1984). This disease is an inherited autosomal recessive disorder characterized by a progressive accumulation of copper, predominantly in the liver (Hardy 1984;Johnson et al 1980).…”
Section: Introductionmentioning
confidence: 93%